2022
DOI: 10.1177/23259671221110208
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Affecting Intercollegiate Water Polo Athletes: A Descriptive Epidemiologic Study

Abstract: Background: There are few data on injuries suffered by collegiate water polo athletes. Purpose: To describe the epidemiology of injuries suffered by National College Athletic Association (NCAA) male and female water polo players by using injury surveillance data over a 5-year period. Study Design: Descriptive epidemiology study. Methods: Deidentified data on all water polo injuries and illnesses recorded in the Pac-12 Sports Injury Research Archive from July 2016 through June 2021 were obtained and analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Finally, this study focuses on female players only, and the results cannot be generalized to male players. 36 Nevertheless, Schroeder et al 14 found no significant difference in concussion rates between both sexes in NCAA athletes, and therefore we speculate that rates in elite males may be similar to elite female players.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Finally, this study focuses on female players only, and the results cannot be generalized to male players. 36 Nevertheless, Schroeder et al 14 found no significant difference in concussion rates between both sexes in NCAA athletes, and therefore we speculate that rates in elite males may be similar to elite female players.…”
Section: Discussionmentioning
confidence: 62%
“…More recently, a retrospective chart analysis of 307 NCAA collegiate water polo players (142 males) competing in the western United States between 2016 and 2021 found that concussions were the most prevalent diagnosis among injured players, affecting 63 athletes (20.5% prevalence). 14…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After receiving institutional review board approval for the study protocol and given our institution’s membership in the Pac-12, we queried the Pac-12 Sports Injury Research Archive between 2017 and 2020 in the same fashion as prior studies. 34 , 37 Included for analysis were all male and female collegiate gymnasts from Pac-12 universities (2 men’s teams and 8 women’s teams) who had a documented “injury event” as reported by a physician, athletic trainer, or physical therapist during either practice or competition, both in season and out of season. “Athletes affected” was defined as the number of athletes who experienced ≥1 recorded injury during the study period.…”
Section: Methodsmentioning
confidence: 99%